2013
DOI: 10.3390/v5082043
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral Infections in Sheep and Goats: Small Ruminant Lentiviruses and Host Interaction

Abstract: Small ruminant lentiviruses (SRLV) are members of the Retrovirus family comprising the closely related Visna/Maedi Virus (VMV) and the Caprine Arthritis-Encephalitis Virus (CAEV), which infect sheep and goats. Both infect cells of the monocyte/macrophage lineage and cause lifelong infections. Infection by VMV and CAEV can lead to Visna/Maedi (VM) and Caprine Arthritis-Encephalitis (CAE) respectively, slow progressive inflammatory diseases primarily affecting the lungs, nervous system, joints and mammary glands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 127 publications
0
44
0
2
Order By: Relevance
“…Approaching potential genetic factors for MV susceptibility from a different point of view, existing data in diverse species indicated that CCR5 could be a candidate gene for resistance to various pathogens [ 16 , 22 27 ]. Even more important in the context of this study is that humans carrying CCR5 variants seem not to acquire human immunodeficiency virus (HIV) [ 28 30 ], the best-explored lentivirus.…”
Section: Introductionmentioning
confidence: 99%
“…Approaching potential genetic factors for MV susceptibility from a different point of view, existing data in diverse species indicated that CCR5 could be a candidate gene for resistance to various pathogens [ 16 , 22 27 ]. Even more important in the context of this study is that humans carrying CCR5 variants seem not to acquire human immunodeficiency virus (HIV) [ 28 30 ], the best-explored lentivirus.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is indication for association between TMEM154 mutations and control of MVV infection, there is no proven association for all the haplotypes [73]. Other genes associated with virus susceptibility are the DPPA2 (Developmental Pluripotency Associated 2)/DPPA4 (Developmental Pluripotency Associated 4), SYTL3 (Synaptotagmin-Like 3), CCR5 (Chemokine receptor 5), MHC (Major Histocompatability Complex), TLR7, TLR8, TLR9 (Toll-like receptors) genes, and APOBEC3 (Apolipoprotein B mRNA-editing enzyme) proteins [75][76][77], whereas the zinc finger cluster, C19orf42 (Chromosome 19 Open Reading Frame 19)/TMEM38A (Transmembrane Protein 38A) and DLGAP1 (Discs Large (Drosophila) Homolog-Associated Protein 1) genes may be used in genetic selection programs to facilitate the control of the disease [78]. The tripartite motif-containing 5 (TRIM5) protein has been studied and has been proved to contribute to the restriction of MVV [79].…”
Section: Risk Factorsmentioning
confidence: 99%
“…[7][8][9]12 Future discoveries and advances in understanding the biology of SRLV-host interactions are essential in identifying means to control viral transmission, the resultant disease manifestation, or both.…”
Section: Host Geneticsmentioning
confidence: 99%